A three phase photovoltaic grid tied inverter system control based on t-s fuzzy equalization - Jameel Kaduim Abed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper proposed a Takagi-Sugeno fuzzy control method is used to build the model for current controlled of three phase photovoltaic inverter. The three phase inverter connected to grid with L filter. The DC link capacitor is splatted midpoint of three phase four wire and the DC link voltage in the input side of the inverter is considered as input variables value for maximum value of the reference current for the feedback controlled. The proposed of T-S fuzzy control method and hysteresis current control can solve and enhance the THD of the output current of the inverter. The T-S fuzzy is designed to monochrome controller makes the output currents are balanced and decrease the harmonic compensation of the full system. The Matlab simulations and test results show the THD, current and the voltage of the three photovoltaic inverter under T-S fuzzy controller method is current balancing efficiency. The control unit is capable of carrying out operation in good condition, dynamic characteristics stable and high quality.